Surgical Therapy Of Ulnaris Nerve Entrapment In Cubital Tunnel Syndrome - Widya Lestari Ningsih Husain; Sidrah Darma; Nikmawati, Nikmawati (Sean Institute, 2025)
This case report describes the condition of ulnar nerve compression that occurs after closed reduction of elbow dislocation, which is a fairly rare complication but can cause upper limb dysfunction if not treated properly. In this case, it is emphasized the importance of making an accurate diagnosis through clinical and supporting examinations so that treatment can be given quickly and appropriately. A pinched ulnar nerve after dislocation can cause symptoms such as tingling, pain, and muscle weakness in the hand area innervated by the nerve. Therefore, this report not only highlights the process of identifying and diagnosing cubital tunnel syndrome, but also discusses the success of surgical intervention in the form of ulnar nerve release performed on the patient. In addition, more optimal results were also achieved through a planned postoperative immobilization and rehabilitation program, which helped accelerate the recovery of nerve function and reduce the risk of recurrence. Rehabilitation that includes range of motion exercises, muscle strengthening, and patient education are important factors in the overall healing process. Thus, this report provides a comprehensive overview of the importance of holistic treatment starting from diagnosis, operative measures, to rehabilitation in cases of cubital tunnel syndrome after elbow dislocation.